Autophagy and Disease: always two sides to a problem - Sridhar, Sunandini (2011)
Autophagy is a process traditionally known to contribute to cellular cleaning through the removal of intracellular components in lysosomes. In recent years, the intensive scrutiny that autophagy has been subjected to at the molecular level, has also contributed to expand our understanding of the physiological role of this pathway. Added to the well-characterized role in quality control, autophagy has proven important in the maintenance of cellular homeostasis and of the energetic balance, in cellular and tissue remodeling and in the cellular defense against extracellular insults and pathogens. It is not a surprise that in light of this growing number of physiological functions, connections between autophagic malfunctioning and human pathologies have also been strengthened. In this review, we focus on several pathological conditions associated to primary or secondary defects in autophagy, and comment on a recurring theme for many of them, that is the fact that autophagy can often exert both beneficial and aggravating effects on the progression of disease. Elucidating the factors that determine the switch between these dual functions of autophagy in disease has become a priority when considering the potential therapeutic implications of the pharmacological modulation of autophagy in many of these pathological conditions.